Brazil chestnut exports from Perú to the United States and the economic factors that influence their variation (Revista Científica Compendium, 2021)
The objective of this research is to carry out an analysis of the economic factors that influenced the Amazon chestnut exports from Peru to the US, with economic data from 2015 to 2020. The study is one of an applied, descriptive type with longitudinal design, using the database expressed in current terms of the Central Reserve Bank of Peru (BCRP) and the Ministry of Agrarian Development and Risk (MINAGRI), through the document review technique and the use of an observation guide based on the pre-established indicators on Amazon chestnut exports per year. The research answered the question about economic factors, transforming current quantities into constants in order to consider price variations and seasonality inherent to the item. It was possible to demonstrate that the existing relationship of the factors (production of external competitors, the exchange rate and internal production) are those that explain the variation in the chestnut exports, in addition to checking their influence statistically on shipments made from Peru to the US market.
Keywords: exports; chestnuts; economic factors; growth